THE EFFECT OF AIR GAP DISTANCE VARIATION BETWEEN STATOR AND ROTOR IN PERMANENT MAGNET GENERATOR WITH LOW ROTATION MULTI-DISC AXIAL FLUX - Yusuf Ismail Nakhoda; Choirul Saleh (Merdeka Malang University, 2020)
This axial flux permanent magnet generator was designed in low speed multi-disc using two stator discs and three rotor discs, wherein each rotor disc contained ten poles of Neodynium type permanent magnet and each stator had ten coils, in order to be able to produce 600 rpm generator rotation. The voltage prepared in each stator phase output would later be connected in series or parallel circuit for testing. This generator was tested with variations of air gap between different rotors and stators. There were four variations of air gap which were 2 mm, 3 mm, 4 mm, and 5 mm and each of them were connected to stator circuit in series. The test results with an air gap of 2 mm generated voltage of 59 Volt AC, an air gap of 3 mm generated a voltage of 53.7 Volt AC, an air gap of 4 mm generated a voltage of 49.6 Volt AC, an air gap of 5 mm generated a voltage of 48.5 Volt AC. Based on the test results, it can be concluded that the gap of the air gap was inversely proportional to the output voltage, the greater the value of the air gap that was applied, the smaller the voltage generator output was generated.